Use of orientation by behavior therapists (Brazilian Journal of Behavioral and Cognitive Therapy, 2002)
Behavior therapists provide rules (Skinner, 1989) and they are considered directive. Is thus orientation the main procedure followed by behavior therapists? Frequency of orientations (behavior description with explicit or implicit consequences) given by experienced behavior therapists was counted as well as the kind of orientation: orientation for action, for reflection or task orientation and also if they were specific or generic. One therapist taped 11 sessions with four clients, another nine sessions with two clients and a third one seven sessions with three clients. All therapists showed a low proportion of verbalizations with orientation, indicating that this was a not often used strategy. The fluctuations indicated negligible differences among therapists and clients. The orientations tended to be specific, the greatest differences among therapists was in the type of orientation given.